Integration of Manipulative Media in Numeracy Learning in Madrasah Ibtidaiyah: Contribution to Islamic Basic Education - M. Ainul Mas'udin RA; Mokhammad Khosim (Attanwir : Jurnal Keislaman dan Pendidikan, 2025)
Students' difficulties in understanding the concept of numeracy are often a challenge in learning mathematics at the primary education level, especially when the methods used are conventional and do not involve direct interaction. This study aims to explore the application of manipulative media as an innovative alternative in numeracy learning in 1st grade students of MI Ar-Rochmah Gesang Tempeh Lumajang. Manipulative media is expected to be able to present a more interesting and meaningful learning experience, so that students not only understand concepts in the abstract but also through physical involvement and active exploration. This research focuses on three main things: first, how the learning process of calculating with manipulative media is carried out in the classroom; second, the impact of the application of this media on the understanding of concepts and student learning outcomes; and third, the various challenges faced during the implementation of the method. These three aspects are the basis for understanding the effectiveness of manipulative media as well as evaluating the obstacles that need to be overcome to create more optimal learning. The research approach uses qualitative methods with case studies as the main design. Data collection techniques involve observation, interviews, and documentation, which aim to dig into the hands-on experiences of teachers and students. Data analysis was carried out through a thematic approach to identify patterns that emerge in learning interactions and their impact on students. The results of the study show that manipulative media is able to significantly increase student involvement in the learning process, create a pleasant atmosphere, and help students understand the concept of counting more easily. However, challenges such as time constraints and the need to improve teachers' competence in utilizing manipulative media were also identified. These findings offer new insights into the importance of innovation in mathematics learning, particularly in the Madrasah Ibtidaiyah environment, to support the achievement of better learning outcomes.